Iterative approximation of a solution of a general variational-like inclusion in Banach spaces - C. E. Chidume; K. R. Kazmi; H. Zegeye (International Journal of Mathematics and Mathematical Sciences)
We introduce a class of η-accretive mappings in a real Banach space and show that the η-proximal point mapping for η-m-accretive mapping is Lipschitz continuous. Further, we develop an iterative algorithm for a class of general variational-like inclusions involving η-accretive mappings in real Banach space, and discuss its convergence criteria. The class of η-accretive mappings includes several important classes of operators that have been studied by various authors.